Effects of Injection Pressure on Output Power, BTE, SFC and Opacity in a Typical Single-Cylinder Diesel Engine - Farid Majedi; Denik Setiyaningrum; Setyono M. T. Hidayahtullah; Aries Abbas (Universitas Muhammadiyah Magelang, 2020)
On a single-cylinder diesel engine, injection pressure can be adjusted by changing the thickness of the injector shim. In this study, the injection pressure of 180 bar (standard), 190 bar (+1mm shim), and 210 bar (+2mm shim) was examined on a typical single-cylinder diesel engine with pure diesel fuel. The tests carried out at a constant engine speed of 1500 rpm with load variations of 650, 1300, 1950, and 3600 Watts to investigate the effect of injection pressure on output power, brake thermal efficiency (BTE), specific fuel consumption (SFC) and opacity. The results showed that increasing injection pressure could increase the output power by 19.3% and 17.4% by adding 1 mm and 2 mm shims, respectively. SFC decreased 1.97% and 12.3% compared to standard conditions and opacity with 2 mm shim was lower than 1 mm shim. In conclusion, increasing the injection pressure from 180 to 210 bar by adding 2 mm shim can improve the performance of a single cylinder diesel engine, which includes output power, brake thermal efficiency (BTE), specific fuel consumption (SFC) and opacity.